2017
DOI: 10.4149/neo_2017_501
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclides in radiation-induced bystander effect; may it share in radionuclide therapy?

Abstract: For many years in radiobiology and radiotherapy predominated the conviction that cellular DNA is the main target for ionizing radiation, however, the view has changed in the past 20 years. Nowadays, it is assumed that not only directed (targeted) radiation effect, but also an indirect (non-targeted) effect may contribute to the result of radiation treatment. Non-targeted effect is relatively well recognized after external beam irradiation in vitro and in vivo, and comprises such phenomena like radiation-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 87 publications
(115 reference statements)
0
17
0
Order By: Relevance
“…When 131 I accumulates in the remnant thyroid tissue, its decay results in thyroid cancer cells’ high energy deposition and minimal irradiation of the surrounding normal tissues. The expression of TNF-α and TIMP-1 is increased after irradiation [ 12 , 13 , 28 ] and can be involved in the 131 I-induced bystander effect. Similar to the previously mentioned studies [ 12 , 13 , 28 ], our results showed that 131 I intake led to a 3.55-fold increase in TNF-α and a 1.19-fold in TIMP-1 in patients without AIT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When 131 I accumulates in the remnant thyroid tissue, its decay results in thyroid cancer cells’ high energy deposition and minimal irradiation of the surrounding normal tissues. The expression of TNF-α and TIMP-1 is increased after irradiation [ 12 , 13 , 28 ] and can be involved in the 131 I-induced bystander effect. Similar to the previously mentioned studies [ 12 , 13 , 28 ], our results showed that 131 I intake led to a 3.55-fold increase in TNF-α and a 1.19-fold in TIMP-1 in patients without AIT.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TNF-α and TIMP-1 is increased after irradiation [ 12 , 13 , 28 ] and can be involved in the 131 I-induced bystander effect. Similar to the previously mentioned studies [ 12 , 13 , 28 ], our results showed that 131 I intake led to a 3.55-fold increase in TNF-α and a 1.19-fold in TIMP-1 in patients without AIT. Moreover, the involvement of TNF-α and the MMP-9/TIMP-1 complex in the radiation-induced non-targeted effects has been demonstrated by the highly statistically significant correlations measured between TNF-α and TIMP-1 (r = 0.68, p < 0.001) and TNF-α and the MMP-9/TIMP-1 ratio (r = −0.66, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inflammatory molecules provide the necessary signals for the recruitment and stimulation of dendritic cells (DC) and macrophages (M) to properly present TAA to helper (CD4+) and cytotoxic T (CTL) lymphocytes, which may target and kill residual and metastatic tumor cells bearing TAA on their surface membrane. The figure is uploaded on the net by Maria Widel and was reproduced with her permission [ 18 ] …”
Section: Tumor Immune Evasionmentioning
confidence: 99%
“…Lastly, also not to be forgotten are the so-called abscopal and bystander effects, which describe effects only indirectly related to radiation exposure such as an activation of the immune system to non-irradiated foci in response to damage incurred by irradiated foci. These effects show both a high degree of heterogeneity and still are poorly understood [17].…”
mentioning
confidence: 99%